PENGEMBANGAN USAHA 2N MELALUI PLATFORM INSTAGRAM DAN WHATSAPP - Putri, Silvia Usmayanti; Habiba, Meilany Pramesti; Falefy, Kurnia Yulia Ayu; Riza, Sayyida Nafisatur; Diniati, Bintis Tianatud (Universitas Kadiri, 2024)
Abstract: This research aims to develop an effective marketing strategy for salted egg Micro,Small and Medium Enterprises (MSME) centers in Kedungsoko Village, Tulungagung District.The problems faced by MSMEs involve limited market access and the lack of use of digitalmarketing to increase the visibility of their products. The research method used wasqualitative, this research involved interviews with MSME owners. The research results showedthat the adoption of digital marketing strategies significantly increased exposure to salted eggMSME products. Through the use of social media, websites and e-commerce platforms, MSMEshave succeeded in reaching a wider market and increasing sales of their products.Keywords: Digital Marketing, Marketing Strategy, and Salted Egg MSMEs